Susceptibility of Anopheles Mosquitoes to Insecticides Used In Busia and Tororo Districts, Eastern Uganda - Chemutai, Faith; Kisakye, Joseph; Kabbale, Fredrick; Egeru, Anthony (Research Square, 2022)
This study assessed the susceptibility of Anopheles mosquitoes to LLINs and IRS as vector control interventions used in Tororo and Busia district. Samples of Anopheles mosquito larvae were collected from various breeding grounds and reared in an insectary. Emerged adults were dissected under a stereoscopic microscope and identified using standardized morphological keys after respective bioassays on used LLINs and sprayed walls. A One-Way Analysis of Variance (ANOVA) was used to test for significant differences in the mean composition of mosquito species across the study area, mean variations, mortalities by net and wall type. Results showed that the Anopheles gambiae sensu lato revealed a higher mean of 78.33 ± 41.52, compared to Anopheles funestus (16.42 ± 24.87) which was lonely found in Busia district. Out of four brands of nets tested for insecticides susceptibility, 99% mortality was recorded for the insecticide concentration of 80 mg/m2 deltamethrin impregnated DAWA plus 2.0 nets. PermaNet 3.0 and Olyset recorded mortality rate of 95% and 93% at chemical concentrations of 50 mg/m2 and 525 mg/m2 permethrin respectively. PermaNet 2.0 recorded 67% mortality at 55 mg/m2 permethrin. The average number of Anopheles mosquitoes were more susceptible to 12.5 mg/m2 of Fludora fusion impregnated onto plastered painted walls at a rate of 100% as compared to the other types of walls after 2 weeks (6.86 ± 4.07) and 1 month of chemical spray (6.69 ± 4.01) varied insignificantly (t = 0.175, P = 0.861). Meanwhile, a disaggregated results by time of spray (T0 and T1) and exposure periods, showed that plastered painted wall, had higher mortalities followed by Brick Plain and Mud/Wattle wall substrates, respectively. This study has shown that vector behavior, biology and physiology need consistent monitoring and surveillance for further entomological characterization and the need for coming up with new vector control interventions.
Keywords: Knocked down; Sentinel areas; Susceptibility; Oscillation; Plasmodium vector